2016
DOI: 10.5152/ucd.2015.3132
|View full text |Cite
|
Sign up to set email alerts
|

Sportsman hernia; the review of current diagnosis and treatment modalities

Abstract: Groin pain is an important clinical entity that may affect a sportsman's active sports life. Sportsman's hernia is a chronic low abdominal and groin pain syndrome. Open and laparoscopic surgical treatment may be chosen in case of conservative treatment failure. Studies on sportsman's hernia, which is a challenging situation in both diagnosis and treatment, are ongoing in many centers. We reviewed the treatment results of 37 patients diagnosed and treated as sportsman's hernia at our hospital between 2011-2014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Several studies report a significant improvement after 6–8 weeks of physical therapy ( Kachingwe and Grech, 2008 ; Woodward et al., 2012 ), which may allow the athlete to return to play. Indeed, most of these therapies involve a period of absence from professional activity, during which the physical therapy was performed ( Cohen et al., 2016 ; Elattar et al., 2016 ; Ellsworth et al., 2014 ; Paksoy and Sekmen, 2016 ). In the present study, where conservative therapy was complemented by the use of CFAs, interruption of the professional activity was not needed, unless a traumatic injury occurred, and thus, the AP symptoms were treated during the season activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report a significant improvement after 6–8 weeks of physical therapy ( Kachingwe and Grech, 2008 ; Woodward et al., 2012 ), which may allow the athlete to return to play. Indeed, most of these therapies involve a period of absence from professional activity, during which the physical therapy was performed ( Cohen et al., 2016 ; Elattar et al., 2016 ; Ellsworth et al., 2014 ; Paksoy and Sekmen, 2016 ). In the present study, where conservative therapy was complemented by the use of CFAs, interruption of the professional activity was not needed, unless a traumatic injury occurred, and thus, the AP symptoms were treated during the season activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies 22,23 suggested sportsman's hernia is often associated with other causes of groin pain in the athlete (Table 1).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The literature describes the conjoint area as being best visualized using a plain x-ray with the patient in the flamingo position or with ultrasound. Additionally, CT and MRI may be used, though they are considered inferior to ultrasound [ 30 - 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…If conservative treatment does not alleviate symptoms of groin pain, surgery is recommended. Similar to the repair of an inguinal hernia, a mesh is sutured to the area to provide additional support [ 30 ].…”
Section: Reviewmentioning
confidence: 99%